An experienced surgeon's take on scapho-lunate diastasis with distal radius fracture: What does this mean? Does this influence functional outcome?. Issue 10 (October 2022) - Lans, Jonathan; Lasa, Alejandro; Chen, Neal C.; Dell'Oca, Alberto Fernandez; Jupiter, Jesse B.
Abstract: Radiographic evidence of scapho-lunate diastasis associated with a displaced distal radius fracture has been well recognized yet the clinical significance remains in question. If left untreated, will this progress to both radiographic and clinical changes consistent with intercarpal arthritis? Using the accumulated data of over 400 surgically treated distal radius fractures in the ICUC database, 16 cases of untreated scapho-lunate diastasis were followed on an average of 8 years without evidence of progressive functional or radiographic deterioration. In 50% of these cases, incidental findings of similar scapho-lunate diastasis was noted in the opposite uninjured wrist.